An Analysis on the Choice of Alpha Level in the Osteometric Pair‐matching of the Os Coxa, Scapula, and Clavicle1. Issue 3 (18th July 2017) - Lynch, Jeffrey James
Abstract: This study compares the use of 0.05 and 0.10 alpha levels with the updated osteometric pair‐matching model on two samples of the os coxa, scapula, and clavicle. The samples include the Forensic Data Bank, and the osteometric sorting reference used within the Defense POW/MIA Accounting Agency. Mixed‐effects two‐way analyses of variance were used to analyze bilateral asymmetry in the standard measurements. In total, 3, 793, 566 t ‐tests were conducted for osteometric pair‐matching analysis. The results indicate high levels of exclusion power, and accuracy can be obtained with the os coxa and scapula. The clavicle standard measurements capture too much asymmetry causing a lower exclusion to accuracy ratio for osteometric pair‐matching relative to other elements. Both 0.05 and 0.10 alpha levels provide acceptable levels of performance. A lower alpha level will result in higher accuracy with less exclusion, and a higher alpha level will result in lower accuracy with more exclusions.